Prevention of Violence in Schools Through System of Roles of a "School Policeman" – Dilemmas and Contradictions - Nikolić, Zlatko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2010)
More frequent scenes of violence in schools, school yards and the close vicinity, whose participants are the students of the same schools, led to the realisation that something is wrong and that a radical reaction is necessary. That brought on the concept of "school policeman" and acceptance of its role, even by those hard-core believers of school as autonomous ground in relation to government authorities, in other words, the police. However, first steps and attempts of implementation suffered from so-called "child diseases" prone to every inception, but, with time, it became common practice. Unfortunately, further developments and new occurrences of violence between school children require answers to questions: Is the whole system set up correctly? Does the role of "school policeman" consist only in "patrolling" or should it be a distinctive system of roles, not only a presence of a policeman, that is, patrolling? The theme of this work is, therefore, to search for answers to these dilemmas and contradictions in roles or the role of "school policeman".